Gastric outlet obstruction from duodenal lipoma in an adult - Promise N Wichendu; Amabra Dodiyi-Manuel (Nigerian Journal of Surgery, 2013)
The duodenum is a rare site for gastrointestinal lipoma with less than 230 cases reported in the literature. Although, peptic ulcer disease remains the most common benign cause of gastric outlet obstruction (GOO), duodenal lipomas remain a rare, but possible cause of GOO and could pose a diagnostic challenge, especially in countries where access to endoscopy and modern imaging techniques poses a challenge. The authors present a case of GOO in a 40-year-old male, secondary to a duodenal lipoma. It was successfully treated by a transduodenal resection through a midline laparotomy. The histology report confirmed it was a submucosal lipoma.